Subacute nodular migratory panniculitis, a rare presentation of a rare disease: a case report - Gupta, Dhruv A.; Agarwal, Pooja; Chaudhary, Raju G.; Baxi, Kalgi (International Journal of Research in Dermatology, 2023)
Panniculitis refers to the inflammation of the subcutaneous fat. Subacute nodular migratory panniculitis (Aka Vilanova disease) is a rare type of panniculitis seen predominantly in women. Clinically, it closely resembles erythema nodosum but is often unilateral as opposed to the bilateral involvement in erythema nodosum. Triggering factors include infections, drugs, thyroid disorders, pregnancy, or malignancies. We report a rare case of a 52-year-old female who was a known case of hypothyroidism and presented with sudden onset of red colored painful lesions with raised temperature over both lower limbs. Hematological evaluation was unremarkable except for raised erythrocyte sedimentation rate. Histopathological examination of the lesion showed septal panniculitis with giant cells, suggestive of subacute nodular migratory panniculitis. The patient responded very well to treatment with capsule indomethacin.